2019
DOI: 10.3363/prb.35.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Modification of Hydroxyapatite/Zeolite Composite on Malodors Adsorption Behavior

Abstract: Hydroxyapatite (HAp)/zeolite composite (HZc) was prepared by a simple immersion method, and it was then modified with Cu 2+ and 3-aminoplopyltriethoxysilane (APES) to produce a novel adsorbent for unpleasant odors such as NH 3 , H 2 S and CH 3 CHO gases. The obtained materials were characterized by SEM-EDS, XRD, FT-IR, TG-DTA and ninhydrin reaction test. Nano-sized order HAp was observed distributed on zeolite for HZc, and modification of HZc with Cu 2+ and APES maintained the original framework structure of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The HA-zeolite composite is used as an adsorbent composite to remove cobalt ions from aqueous solutions. They report that HA-zeolite composites have better surface adsorption compared to pure HA which is around 65% of cobalt (II) in pH close to 6 and temperatures around 30 o C. The level of surficial adsorption lower by metal ion content [53,54]. It has been earlier reported that the porous apatite layer can strengthen the application of bone tissue engineering [55].…”
Section: Morphology Of Hydroxyapatite-zeolite Compositementioning
confidence: 98%
See 1 more Smart Citation
“…The HA-zeolite composite is used as an adsorbent composite to remove cobalt ions from aqueous solutions. They report that HA-zeolite composites have better surface adsorption compared to pure HA which is around 65% of cobalt (II) in pH close to 6 and temperatures around 30 o C. The level of surficial adsorption lower by metal ion content [53,54]. It has been earlier reported that the porous apatite layer can strengthen the application of bone tissue engineering [55].…”
Section: Morphology Of Hydroxyapatite-zeolite Compositementioning
confidence: 98%
“…Biocompatibility is evaluated and shows the presence of silica biocompatible behavior which is increased by the presence of HA in nanocomposites. The adsorption ability of HA-zeolite composites produced by the precipitation method has been evaluated by Nishida et al [53]. The HA-zeolite composite is used as an adsorbent composite to remove cobalt ions from aqueous solutions.…”
Section: Morphology Of Hydroxyapatite-zeolite Compositementioning
confidence: 99%
“…It was hypothesized that the adsorption capaci of Cu-HA was related to the electronic structure of copper in the crystal lattice. In a follow up work authored by Nishida et al [333], a composite material of HA and zeolite w prepared and subsequently functionalized with Cu 2+ and amino groups. It was found th the copper-doped composites have an excellent adsorption capacity for H2S and NH gases, and the amino functionalization also imparted a good adsorption capacity f Reprinted with permission from [332]).…”
Section: Deodorantsmentioning
confidence: 99%
“…In our previous study, the natural Itaya zeolite-related material in which divalent copper ion was supported showed drastic and decent enhancement of ability to adsorb NH 3 and H 2 S gases, respectively. 1) These findings have motivated us to fabricate a practical deodorant product containing natural zeolite, which can be mainly applied to a part of interior building materials such as tiles. To solidify the zeolite powder into a three-dimensional continuum with a certain size and strength, it must be encased with the aid of inorganic cementitious binders.…”
Section: Introductionmentioning
confidence: 99%